Arabidopsis AGDP1 links H3K9me2 to DNA methylation in heterochromatin. Issue 1 (December 2018) - Zhang, Cuijun; Du, Xuan; Tang, Kai; Yang, Zhenlin; Pan, Li; Zhu, Peipei; Luo, Jinyan; Jiang, Yuwei; Zhang, Hui; Wan, Huafang; Wang, Xingang; Wu, Fengkai; et al.
Abstract Heterochromatin is a tightly packed form of chromatin that is associated with DNA methylation and histone 3 lysine 9 methylation (H3K9me). Here, we identify an H3K9me2-binding protein, Agenet domain (AGD)-containing p1 (AGDP1), inArabidopsis thaliana . Here we find that AGDP1 can specifically recognize the H3K9me2 mark by its three pairs of tandem AGDs. We determine the crystal structure of the Agenet domain 1 and 2 cassette (AGD12) ofRaphanus sativus AGDP1 in complex with an H3K9me2 peptide. In the complex, the histone peptide adopts a unique helical conformation. AGD12 specifically recognizes the H3K4me0 and H3K9me2 marks by hydrogen bonding and hydrophobic interactions. In addition, we find that AGDP1 is required for transcriptional silencing, non-CG DNA methylation, and H3K9 dimethylation at some loci. ChIP-seq data show that AGDP1 preferentially occupies long transposons and is associated with heterochromatin marks. Our findings suggest that, as a heterochromatin-binding protein, AGDP1 links H3K9me2 to DNA methylation in heterochromatin regions. DNA methylation and H3K9 dimethylation are two linked epigenetic marks of silenced chromatin in plants that depend on the activity of CMT3/2 and SUVH4/5/6. Here the authors identify AGDP1 as an H3K9me2-binding protein required for heterochromatic non-CG DNA methylation, H3K9 dimethylation, and transcriptional silencing.